Evidence of short timescale flux density variations of UC H II regions in SGR B2 MAIN and North - Pree, Christopher G. De; Peters, T.; Low, M. M. Mac; Wilner, D. J.; Goss, W. M.; Galván-Madrid, R.; Keto, E. R.; Klessen, Ralf S.; Monsrud, A. (The astrophysical journal, 2015)
We have recently published observations of significant flux density variations at 1.3 cm in H ii regions in the star-forming regions Sgr B2 Main and North. To further study these variations, we have made new 7 mm continuum and recombination line observations of Sgr B2 at the highest possible angular resolution of the Karl G. Jansky Very Large Array (VLA). We have observed Sgr B2 Main and North at 42.9 GHz and at 45.4 GHz in the BnA configuration (Main) and the A configuration (North). We compare these new data to archival VLA 7 mm continuum data of Sgr B2 Main observed in 2003 and Sgr B2 North observed in 2001. We find that 1 of the 41 known ultracompact and hypercompact H ii regions in Sgr B2 (K2-North) has decreased ∼27% in flux density from 142 ± 14 to 103 ± 10 mJy (2.3σ) between 2001 and 2012. A second source, F3c-Main, has increased ∼30% in flux density from 82 ± 8 to 107 ± 11 mJy (1.8σ) between 2003 and 2012. F3c-Main was previously observed to increase in flux density at 1.3 cm over a longer time period between 1989 and 2012. An observation of decreasing flux density, such as that observed in K2-North, is particularly significant since such a change is not predicted by the classical hypothesis of steady expansion of H ii regions during massive star accretion. Our new observations at 7 mm, along with others in the literature, suggest that the formation of massive stars occurs through time-variable and violent accretion.
Gesehen am 23.12.2020